Morphology of Nylon 6/Acrylonitrile-Butadiene-Styrene Blends Compatibilized by a Methyl Methacrylate/Maleic Anhydride Copolymer - Araújo, E. M.; Hage, E.; Carvalho, A. J. F. (Wiley, 2003)
The morphologies of nylon 6/acrylonitrile-butadiene-styrene blends compatibilized with a methyl methacrylate/maleic anhydride copolymer, with 3-20 wt % maleic anhydride, were examined by transmission electron microscopy. Some staining techniques were employed for identifying the various phases. The binary blends were immiscible and exhibited poor mechanical properties that stemmed from the unfavorable interactions among their molecular segments. This produced an unstable and coarse phase morphology and weak interfaces among the phases in the solid state. The presence of the copolymer in the blends clearly led to a more efficient dispersion of the acrylonitrile-butadiene-styrene phase and consequently optimized Izod impact properties. © 2003 Wiley Periodicals, Inc.
Keywords: Blends; Compatibilization; Morphology; Nylon; ABS resins; Copolymers; Interfaces (materials); Nylon polymers; Transmission electron microscopy; Staining techniques; Polymer blends; copolymer; morphology; nylon 6